2013
DOI: 10.1111/apm.12203
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ErbB-2 induces TFF3 downregulation in breast cancer cell lines

Abstract: ErbB-2 gene plays an important role in carcinoma formation whose overexpression was observed in many types of tumors, including breast cancer. Dysregulation of Trefoil factor 3 (TFF3), which is thought to function in the development and progression of breast cancer, was found to be upregulated in ErbB2-overexpressing breast cancers and cells. However, a putative interaction between ErbB-2 and TFF3 in breast cancer remains unknown. To determine whether TFF3 has an important role in breast tumor, its levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Our current findings are consistent with these observations in that HER2 transcriptionally represses TFF3, while trastuzumab inhibition of HER2 releases the transcriptional repression on TFF3 in HER2+/ER+ breast cancer cells. In contrast to our findings of trastuzumab-stimulated upregulation of TFF3 in BT474 cells, Yue et al observed that the silencing of HER2 induced TFF3 downregulation in HER2+/ER− SKBR3 cells [ 65 ]. This discrepancy may be attributed to two reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…Our current findings are consistent with these observations in that HER2 transcriptionally represses TFF3, while trastuzumab inhibition of HER2 releases the transcriptional repression on TFF3 in HER2+/ER+ breast cancer cells. In contrast to our findings of trastuzumab-stimulated upregulation of TFF3 in BT474 cells, Yue et al observed that the silencing of HER2 induced TFF3 downregulation in HER2+/ER− SKBR3 cells [ 65 ]. This discrepancy may be attributed to two reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…A relationship of HER-2 and TFF3 has been confirmed in a breast cancer study, which identified TFF3 expression to be strictly associated with HER2 amplification in SK-BR-3 cells. 2 A meta-analysis study revealed that HER2 overexpression/amplification is one of the fundamental pathogenetic pathways in patients affected by EMPD. The TFFs could be applied as therapeutic targets based on their role in the biological processes.…”
Section: Overexpression Of Trefoil Factor 1 and Trefoil Factor 3 In Primary Extramammary Paget's Disease And Implication Of A Novel Theramentioning
confidence: 99%